Genome Analysis of Lactobacillus plantarum Isolated From Some Indian Fermented Foods for Bacteriocin Production and Probiotic Marker Genes - Goel, Aditi; Halami, Prakash M.; Tamang, Jyoti Prakash (Frontiers in Microbiology, 2020)
In this study Lactobacillus plantarum strain DHCU70 isolated from dahi, a fermented milk product and L. plantarum strain DKP1 isolated from kinema, a fermented soybean food of India, respectively were evaluated for their bacteriocin production and probiotic properties. Both strains of L. plantarum (DHCU70 and DKP1) were found to have potent antimicrobial activity against Kocuria rhizophila ATCC 9341. Bacteriocin produced by L. plantarum strains DHCU70 and DKP1 did not exhibit inhibition of cell wall, DNA and fatty acids biosynthesis mechanisms as evaluated by whole cell reporter assays. We characterized the bacteriocin encoding genes in L. plantarum strains DHCU70 and DKP1 by whole genome sequence which consisted of a single and circular chromosome with genome size of 3.38Mb (GC content of 44.3%) and 3.39Mb, respectively and a GC content of 44.3%. L. plantarum DHCU70 has 3252 number of protein encoding genes comprising 89 number of RNA genes (69 tRNA, 16 rRNA, 4 nc RNA) whereas L. plantarum DKP1 has total of 3277 number of protein encoding genes with 89 number. of RNA genes (69 tRNA, 16 rRNA, 4 nc RNA). Analysis revealed the presence of 20.5kb long and 23 numbers of plantaricin encoding locus (pln locus) for production of antimicrobial compound. BAGEL analysis has shown that the pln locus of both the strains of L. plantarum showed maximum sequence similarity with plantaricin NC8 of L. plantarum NC8, originally isolated from grass silage. Annotated whole genome sequence of both strains DHCU70 and DKP1 was analysed for the presence of probiotic marker genes. The probiotic properties of these strains of were also evaluated in vitro. Due to the presence of genes responsible for antimicrobial activity and probiotic properties, both strains of L. plantarum may be considered as a suitable probiotic candidate in food industry.